Vaporized Cannabis Is Effective and Well-Tolerated in an Adolescent with Tourette Syndrome - Natalia Szejko; Ewgeni Jakubovski; Carolin Fremer; Kirsten R. Müller-Vahl (Medical Cannabis and Cannabinoids)
We present the case of a 12-year-old boy diagnosed with Tourette syndrome, who was successfully treated with a combination of vaporized medicinal cannabis and oral pure tetrahydrocannabinol (THC). Due to severe motor tics resulting in insomnia, the parents – both of whom were medical doctors – decided to initiate treatment with 0.02 g vaporized cannabis (Bedrocan with a THC content of 22% and a cannabidiol content of 1%; corresponding to a dose equivalent to 4.4 mg THC) without prior consultation of a Tourette expert. This treatment resulted – according to the parents’ report – in an immediate and nearly complete remission of the tics. Due to a further increase in tics, the parents therefore decided to implement a regular treatment with a combination of vaporized medicinal cannabis (up to 0.1 g cannabis per day, varieties Bedrocan and Amnesia Haze, corresponding to 22 mg THC/day) plus orally administered oil-based THC drops (maximum daily dose = 12.5 mg THC) resulting in a marked tic reduction. During a visit in our clinic, we were able to observe the reported beneficial effects 30 min after vaporization of 0.15 g cannabis (Amnesia Haze, equivalent to 33 mg THC; in addition, 7 mg oral THC were taken at home 6 h before the visit): tics, premonitory urges, and overall impairment significantly improved according to self-ratings, parent and clinician questionnaires. Importantly, no adverse events were reported. From this single case study, it is suggested that cannabis-based medicines and their combination (such as oral THC plus vaporized medicinal cannabis) are effective and safe in the treatment of severe tics in minors with TS. However, long-term follow-up is needed to confirm the beneficial treatment effects. We want to emphasize that in this boy treatment with cannabis was initiated by the parents before a consultation in our clinic has taken place. In our opinion, treatment with cannabis-based medicine in children should be regarded as a last-line treatment, when well-established treatments have failed to improve tics.